BAYESIAN COX PROPORTIONAL HAZARDS SURVIVAL ANALYSIS FOR MODELING THE WAITING TIME OF BACHELOR’S DEGREE GRADUATES TO OBTAIN THEIR FIRST JOB(A CASE STUDY OF MATHEMATICS UNDERGRADUATE GRADUATES AT UDAYANA UNIVERSITY) - Juliani Tandi Tumbiri; Ni Luh Putu Suciptawati; Made Susilawati (INJOSEDU: International Journal of Social and Education, 2026)
This study aims to modeling the duration of waiting time for graduates to get their first job, which is generally less than 12 months. The waiting time is influenced by internal and external factors. Internal factors include hardskill and softskill aspects. Hardskills in this study include Grade Point Average (GPA), graduation predicate, academic achievement, TOEFL score. Meanwhile, soft skills are measured through organizational experience. Then the factors outside of hard skills and soft skills are gender and sources of job vacancy information. The analysis was conducted using the Cox Proportional Hazard regression method using a Bayesian approach to understand the influence of each factor on the waiting time for graduates to get their first job. The results showed that gender, sources of information on job vacancies and hard skills did not have a significant effect on the waiting time for graduates to get their first job, while organizational experience had a significant effect in accelerating the waiting time for graduates to get their first job, showing the important role of soft skills in improving readiness and competitiveness in the world of work.